Tinjauan Sistematis untuk Mengoptimalisasi Pengalaman Pengguna Chatbot untuk Akses Layanan Mikro dan Keuangan Mikro pada UMKM - Fawwaz shabri Muttaqi; Agus Juhana (LP2M Universitas Widyatama, 2025)
The objective of this research is to investigate implementation of chatbots in the microfinance and MSME sectors for better user experience and accessibility of public services. Systematic Literature Review (SLR) is applied in this article to review related articles with strict inclusion and exclusion criteria. In this sense, it was identified in an investigation with the aim of finding